Comparative evaluation of immunochromatographic card tests with enzyme-linked immune sorbent assay for the detection of hepatitis C virus antibody - Jain, Rajeev Kumar; Shrivastava, Rakesh; Chaurasia, Deepti; Jain, Anamika; Perumal, Nagaraj (International Journal of Research in Medical Sciences, 2023)
Background: Hepatitis C virus (HCV) is a global prevalent pathogen causes both acute and chronic hepatitis and leading to serious liver damage. Correct and rapid diagnosis is pivotal for the management of HCV disease. Rapid card tests are superior alternatives for the large-scale screening of HCV infection. Methods: The present observational study evaluates analytical performance of four different anti-HCV rapid tests. A total of 200 ELISA confirmed, HCV positive (n=100) and HCV negative (n=100) clinical specimens were selected and re-tested for anti-HCV antibodies by using commercially available four different immunochromatography cards (Meriscreen, Accurate, Oscar and Biolab). Results: Among all, Biolab rapid card test shown highest (98%) sensitivity. On the other hand, all rapid card test kits showed identical 100% specificity. Conclusions: Overall BioLab anti-HCV rapid card tests found to be superior in the present study and strongly suggest in house validation of rapid card tests before their diagnostics use on clinical specimens.